Globalization and development in the Mekong economies - Leung, Suiwah; Bingham, Ben.; Davies, Matt.; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar Pub., 2010)
Since the late 1980s, Vietnam, Cambodia, PDR Lao, and Myanmar have been opening their economies to international trade and investment. With the exception of Myanmar, the reforms have yielded impressive results, but the process is far from complete. In this enlightening book, a group of leading scholars outline the continuing reform efforts needed to survive the current global recession and place these economies in a competitive position on the recovery of the world economy.
pt. 1. Developments in East Asia and the world economy -- pt. 2. Case studies of Mekong countries -- pt. 3. Political economy of reform in the Mekong.
Includes bibliographical references and index.
Keywords: Mekong River Regions -- Economic conditions; Globalization -- Mekong River Regions; Electronic books